Synthesis of Quinazolines and Dihydroquinazolines: o-Iodoxybenzoic Acid Mediated Tandem Reaction of o-Aminobenzylamine with Aldehydes - Hati, Santanu; Sen, Subhabrata (Synthesis, 2016)
We have demonstrated a facile synthesis of diversely substituted quinazolines and 3,4-dihydroquinazolines through the o-iodoxybenzoic acid (IBX) mediated tandem reaction of readily available o-aminobenzylamine and aldehydes. The yield of the reactions generally ranged from 70% to 95%. This mild protocol provides an efficient strategy toward the synthesis of these classes of heterocycles.
Keywords: quinazolines; dihydroquinazolines; o-iodoxybenzoic acid; o-aminobenzylamine; aldehydes